2015
DOI: 10.1093/hmg/ddv337
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous mutation in the eukaryotic translation initiation factor 2alpha phosphatase gene,PPP1R15B, is associated with severe microcephaly, short stature and intellectual disability

Abstract: Protein translation is an essential cellular process initiated by the association of a methionyl–tRNA with the translation initiation factor eIF2. The Met-tRNA/eIF2 complex then associates with the small ribosomal subunit, other translation factors and mRNA, which together comprise the translational initiation complex. This process is regulated by the phosphorylation status of the α subunit of eIF2 (eIF2α); phosphorylated eIF2α attenuates protein translation. Here, we report a consanguineous family with severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 32 publications
0
43
0
Order By: Relevance
“…Interestingly, the VWM syndrome pathology is mainly localized to the brain and ovaries, while MEHMO syndrome is more generalized (though the white matter changes are reminiscent of VWM). In contrast, patients with mutations in PPP1R15B share additional symptoms with the EIF2S3 male mutation carriers including diabetes, severe microcephaly, growth retardation, developmental delay, ID, and bone dysplasia [Abdulkarim et al., ; Kernohan et al., ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the VWM syndrome pathology is mainly localized to the brain and ovaries, while MEHMO syndrome is more generalized (though the white matter changes are reminiscent of VWM). In contrast, patients with mutations in PPP1R15B share additional symptoms with the EIF2S3 male mutation carriers including diabetes, severe microcephaly, growth retardation, developmental delay, ID, and bone dysplasia [Abdulkarim et al., ; Kernohan et al., ].…”
Section: Discussionmentioning
confidence: 99%
“…Earlyonset diabetes and endocrine symptomatology can also be seen in majority of other disorders caused by increased endoplasmic reticulum stress or a dysfunction in the unfolded protein response pathway, i.e. syndromic form of intellectual disability and diabetes caused by mutations in the PPP1R15B (Kernohan et al 2015, Abdulkarim et al 2015 In conclusion, we reported on two patients with MEHMO syndrome with neonatal hypoglycemia followed by early onset diabetes, and hypopituitarism presumably due to dysregulation of protein synthesis and gradual decline of peptide hormone secretion. The genetic analysis of genes involved in protein translation and its regulation needs to be considered in patients with syndromic forms of diabetes and endocrine related syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…MEHMO syndrome Vol. 67 (OMIM# 300148) is characterized by X-linked intellectual disability, epileptic seizures, hypogonadism, hypogenitalism, microcephaly, and obesity (Leshinsky-Silver et al 2002). Diabetes or endocrine phenotypes have not been included to the main signs of the MEHMO syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Kernohan et al [] and Abdulkarim et al [] described a novel recessive syndrome characterized by severe microcephaly, short stature, delayed myelination, and intellectual disability. The latter family also had pediatric diabetes.…”
Section: Discussionmentioning
confidence: 99%